An empirical study : The relationship between personality traits and job performance / Mohamad Firdaus Mustaffa - Mustaffa, Mohamad Firdaus (Faculty of Business and Management, 2017)
This study is concentrated on the relationship between personality traits and job performance at KPDNKK Negeri Pahang. The measurement was completed through several independent variables that consist of Conscientiousness, Agreeableness, Neuroticism and Openness to Experience. Thus, the dependent variable for this research was job performance. The questionnaires have been used in this study to collect the data. The researcher distributes personally the questionnaires to 50 employees at KPDNKK Negeri Pahang. There was 49 sets of questionnaire have been collected. After collecting all the questionnaires, it has been analysed the research questions, research objectives and hypothesis. The sampling technique used in this study is the random sampling technique. Moreover, the Cronbach's Alpha for Conscientiousness was (.640), Agreeableness was (.623), the Neuroticism was (.608) and Openness to Experience was (.680). Lastly, for the Job Performance, the Cronbach's Alpha was (.748). These alphas score showed that the reliability are preferable, since 0.5 and above are considered as the reliable value. The relationship has been discovered between personality traits and job performance is positive and moderate.